THE LIFE AND WORK OF MUHAMMAD AMINXO’JA EXPLORE - Abdurahmonov Abdulaziz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Studying Mukhimiy’s life started while he was alive. Different discussions for his poems can be proof for that. Four years after the death of the poet, his initial completion was published by Nikolai Ostroumov in 1907 under the name “Devoni Muqimiy”. In that completion consisted of not only his poems, there was his brief biography and creation.In 1910 in Portsev lithography was carried out the second edition of the works of the poet with the name” Devoni Muqimiy maa hajviyot". A number of articles were published in newspapers and journals. the auspicious work was carried out by the great poet Gafur Gulom. On his initiative, in 1938 was established and published the “Muqimiy bayozi". In " Bayoz" were given 27 poems of the poet, consisting of 800 lines, which were placed according to the features of the genre (satire-humor, lyrics) and they were given with the necessary explanations, dictionaries.In 1950 the works of the poet were issued in Russian in Moscow under the name ““Lirika i satira”. On the occasion of the 50th anniversary of his death in 1953 a number of studies were created about him and laid the foundation for his studies. H.Yagubov’s "Uzbek poet Mukhimy’, A.Olimjonov’s "Muhammad Amin Mukhimy ", H. Zaripov’s” Muhammad Amin Mukhimy ", H.Razzakov’s books "Mukhimy and Zavkhy“, a collection of articles” were published. This article covers the study of Mukhimy’s life and activities in the textbooks of literature in the pre-Independence period.